Democracy, representation and rights (Andamios, Revista de Investigación Social, 2012)
Democracy lives today a paradoxical situation. Meet an unprecedented and yet there seems to be a widespread discomfort with democracy. Discomfort generated by a chaotic capitalist globalization, dominated by the wild powers of finance and modern media, which require governments to submit to the demands of that metaphysical entity called “the markets”. It is therefore relevant to try to restore and clarify the principles and values of democracy as an ideal form of government to take seriously the fundamental rights as essential preconditions for the rules of democracy are more than the corporate facade unjust, authoritarian and autocratic governments basically.
Keywords: Democracy; representation; fundamental rights; powers savages